2017
DOI: 10.19173/irrodl.v18i5.2991
|View full text |Cite
|
Sign up to set email alerts
|

Learner Behaviour in a MOOC Practice-oriented Course: In Empirical Study Integrating TAM and TPB

Abstract: Few practice-oriented courses are currently integrated into online learning platforms, such as OpenCourseWare, Khan Academy, and Massive Open Online Courses (MOOCs). It is worthwhile to explore how learners respond to information technology and new teaching methods when practice-oriented course are placed online. Therefore, this study probes learner willingness to participate in a practice-oriented course distributed through a MOOC platform, investigating relationships among perceptions, behavioural intentions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 74 publications
(99 reference statements)
9
60
1
2
Order By: Relevance
“…This model has been widely used in a variety of science and technology accepted behavior research, and hypotheses in the model have also been repeatedly verified [21][22][23]. Multiple previous studies also pointed out that TAM has certain explanatory power for the integration of computer assistance instruction (CAI) and information communicational technology (ICT) in teaching [24][25][26][27][28][29]. The research results of TAM indicated that users' attitudes towards the usefulness and easiness of technology products have a positive impact on the acceptance attitude and intention of products and proved that perceptual usefulness and easiness have a positive impact on intentions [30][31][32].…”
Section: Migration Theorymentioning
confidence: 84%
See 1 more Smart Citation
“…This model has been widely used in a variety of science and technology accepted behavior research, and hypotheses in the model have also been repeatedly verified [21][22][23]. Multiple previous studies also pointed out that TAM has certain explanatory power for the integration of computer assistance instruction (CAI) and information communicational technology (ICT) in teaching [24][25][26][27][28][29]. The research results of TAM indicated that users' attitudes towards the usefulness and easiness of technology products have a positive impact on the acceptance attitude and intention of products and proved that perceptual usefulness and easiness have a positive impact on intentions [30][31][32].…”
Section: Migration Theorymentioning
confidence: 84%
“…Step 5-goodness-of-fit (GoF) model fitness index [29,65,[68][69][70]. In addition to evaluating the model predictive power, the effect value f 2 of structural models is also an important measure of performance.…”
Section: Goodness Of Fit and Indices Of Structural Modelmentioning
confidence: 99%
“…Their behaviour looks like 'Targeting" (Madonado-Ahauad et al, 2018), but our students often appeared unable to successfully complete the course. Interpreting this behaviour from perspectives such as the behaviour intention theory might shed light on student motives for enrolling and dropping off (Henderikx et al, 2017;Yang & Su, 2017). clusters 2 and 3 appear to be nuances of the disengaging learners (Kizilcec et al, 2013), with cluster 3 showing somewhat more ordered learning behaviour, and better learning results.…”
Section: Discussionmentioning
confidence: 99%
“…According to the John Dewey's education theory [1], the "learning by doing" approach takes the students as the learning task center. Compared with traditional teaching, it is helpful to mobilize students' learning enthusiasm and get them to participate in the process of teaching and learning, therefore it promotes the integration of the curriculum and fits today's STEM (Science, Technology, Engineering and Mathematics) education thought [13][14][15][16][17][18]. In the task-driven classroom teaching method, we construct suitable learning tasks, measures, requirements, learning environment and conditions, and these guide students to find the best way to solve the problem [7].…”
Section: Research Purposementioning
confidence: 99%
“…In this paper, we design an experimental questionnaire to understand students' learning attitude towards information technology courses and their knowledge. There are 10 multiple-choice questions in the questionnaire [17]. Each choice is based on students' knowledge of information technology and the development of attitude.…”
Section: Instrumentsmentioning
confidence: 99%